The Influence of Internal Marketing Practices on Employee Satisfaction Private Universities in Yogyakarta - Chasanah, Uswatun; Mathori, Muhammad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to evaluate the impact of Internal Marketing dimensions on employee satisfaction. The dimensions analyzed in internal marketing include leadership support, training and development, information and communication, and rewards. This research was conducted in 2022 involving 25 employees from a college in Yogyakarta as respondents. For data analysis, multiple regression and Smart PLS version 3.29 software were used. The analysis results indicate that only the dimension of information and communication has a positive and significant effect on employee satisfaction, thus confirming the hypothesis. Meanwhile, the direct effects of leadership support, training and development, and rewards on job satisfaction were not confirmed.